2008
DOI: 10.1158/0008-5472.can-08-1319
|View full text |Cite
|
Sign up to set email alerts
|

Global Hypomethylation of Genomic DNA in Cancer-Associated Myofibroblasts

Abstract: Global hypomethylation has long been recognized as a feature of the malignant epithelial component in human carcinomas. Here we show evidence for this same type of epigenetic alteration in cancer-associated stromal myofibroblasts. We used methylation-sensitive SNP array analysis (MSNP) to profile DNA methylation in early-passage cultures of stromal myofibroblasts isolated from human gastric cancers. The MSNP data indicated widespread hypomethylation in these cells, with rare focal gains of methylation, conclus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 45 publications
14
127
0
2
Order By: Relevance
“…These libraries represented cell types sampled from one breast cancer patient, implicating the relationship between BCL6 and its antisense transcript in the biology of this individual breast cancer. While carcinoma-associated myofibroblasts are not necessarily cancer cells per se, they have epigenetic alterations similar to those seen in malignant carcinoma epithelium, and are globally hypomethylated (Jiang et al 2008). One plausible explanation for the increase in antisense expression at this locus is increased hypomethylation at CpG islands downstream from the BCL6 gene (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 98%
“…These libraries represented cell types sampled from one breast cancer patient, implicating the relationship between BCL6 and its antisense transcript in the biology of this individual breast cancer. While carcinoma-associated myofibroblasts are not necessarily cancer cells per se, they have epigenetic alterations similar to those seen in malignant carcinoma epithelium, and are globally hypomethylated (Jiang et al 2008). One plausible explanation for the increase in antisense expression at this locus is increased hypomethylation at CpG islands downstream from the BCL6 gene (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Jiang et al detected global hypomethylation of genomic DNA by means of a methylation-sensitive SNP array analysis (MSNP), a restriction enzyme-based analysis, in the stromal myofibroblasts of gastric carcinomas (36). By contrast, when we focused on promoter CGIs in the current study, the results showed a higher number of hypermethylated genes than hypomethylated genes in CAFs (hypermethylated: 188 CGIs in Case 1 and 98 CGIs in Case 2; hypomethylated: 39 CGIs in Case 1 and 50 CGIs in Case 2).…”
Section: Discussionmentioning
confidence: 99%
“…74,75 In our own SNP chip analysis of gastric cancer associated fibroblasts, we did not observe any evidence of genetic alterations. 76 Epigenetic alterations, on the other hand, do seem to be distinct from the epithelium and ubiquitous in the TME. Epigenetic changes, in particular methylation changes, may provide one explanation for how stromal cells maintain the expression differences even after removal from the tumor environment (as has been confirmed in multiple studies in breast, prostate and gastric cancer).…”
Section: Gastric Cancer As a Model Of Inflammation Driven Carcinogenesismentioning
confidence: 99%